Effects of resveratrol against scattered radiation-induced testicular damage in rats - ATASOY, BESTE MELEK; ŞENER, GÖKSEL; KAYA, ÖZLEM TUĞÇE; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (WALTER DE GRUYTER GMBH, 2021)
Objectives: To investigate the possible protective effects of resveratrol against oxidative testicular damage due to scattered radiation during pelvic ionizing radiation exposure in rats. Methods: Rats were divided into 5 groups; control, radiation, and radiation + resveratrol therapy in early and late periods. Under anesthesia, 20 Gy ionizing radiation was applied to prostatic region. Resveratrol was administered (10 mg/kg/day) orally before ionizing radiation exposure. Animals were decapitated at the end of 1st and 10th weeks. Biochemical markers of oxidative stress; caspase-3 and sirtuin-1 protein expressions; testosterone levels were evaluated, histological examinations were performed. Results: Significant increases in malondialdehyde, 8-hydroxy-deoxyguanosine levels, myeloperoxidase, and caspase-3 activities were observed after ionizing radiation exposure, also superoxide dismutase and glutathione activities were significantly decreased. Radiotherapy increased caspase-3 and decreased sirtuin-1 protein expressions. Resveratrol treatment significantly reversed these parameters and also reversed the decrease in testosterone levels back to control levels in late period. Conclusion: Resveratrol showed antioxidant and sirtuin-activating properties against oxidative damage caused by scattered radiation to testis and provided hormonal protection. These results suggest that resveratrol may be an alternative protective agent on testicular tissues against the effects of scattered pelvic radiation.
Keywords: oxidative stress; radiotherapy; resveratrol; sirtuin-1; testis; INDUCED OXIDATIVE STRESS; ERECTILE DYSFUNCTION; SERUM TESTOSTERONE; INJURY; RADIOTHERAPY; MELATONIN